Informality and Competition - Tello, Mario D. (2022)
Based upon the changes of labor productivity for the economy decomposed by sectors and activities, this paper proposes three hypotheses on the relationship between the informal sector and competition for Peruvian economy in the period 2007-2018. The first one postulates that there might exist product market segmentation between formal and informal firms. The second postulates that the effects of the PTAs on the changes of labor productivity in activities and sectors have been diverse and unclear. The last and third hypothesis postulates that labor productivity changes in Peru and its within and reallocation components have been associated with the fluctuations and the rate of growth of the GDP and the terms of trade. These associations are consistent with the primary- export structure of the Peruvian economy.